Laser induced modifications and waveguides writing inside silicon - Wang, Xinya (Kansas State University, 2023)
Silicon is the basic material for semiconductor industry and laser direct writing in the bulk of silicon has attracted people’s attention since 20 years ago. However, the research of laser-matter interaction inside silicon is limited and the formation process of the subsurface modification is not clear enough. In addition, the attempts in the past decade to generate waveguides inside silicon are not satisfactory. Based on this situation, this dissertation has two objectives. The first one is to study the fundamental process of laser-matter interaction and have a better understanding of the material modification process inside silicon, and the second one is to write straight and curved waveguides inside silicon and characterize these waveguides. The first objective will be achieved through a comprehensive experimental study on the physics behind the nanosecond (ns) laser writing process. The experimental study will involve generating subsurface modifications inside silicon and characterize the modifications by optical microscopy, SEM, TEM, and Raman spectroscopy. The second objective will be achieved through laser transverse writing and by shaping the laser beam through a pair of cylindrical lenses and focusing the shaped beam inside the silicon. It is found that permanent modifications are made with tightly focused ns pulses at 1.55 μm wavelength inside silicon without damaging the front surface. Examinations of the modified zone using Raman spectroscopy and TEM reveal a disturbed crystal structure with defects and strained areas. For the first time, high resolution TEM images show a direct evidence of amorphous silicon inside ns laser induced modifications. A quantitative analysis based on Raman spectra of the modified zone indicates that the amorphous silicon accounts for only a small percentage of the total modification. More work is needed to determine the effects of laser parameters on the amorphous transition inside silicon. Nanosecond laser transverse writing of different types of waveguides inside silicon are demonstrated, such as straight waveguides, curved waveguides with different radii, and straight-curved waveguides. A nearly circular transverse guide-profile is formed with the shaped beam. The waveguides are found to support single-mode propagation for 1.55 μm wavelength light. The loss is found to be about 3 dB/cm for straight waveguide and can be larger for curved waveguides depending on the curvature. The knowledge gained from this research will enable us to have a better understanding of laser-matter interaction inside silicon and pave the way for its future applications in the semiconductor field.
Keywords: Laser; Semiconductor; Waveguides; Silicon